Synthesis, characterization, stability and thermal conductivity of multi-walled carbon nanotubes (MWCNTs) and eco-friendly jatropha seed oil based nanofluid: An experimental investigation and modeling approach - Rehman, Wajid Ur; Merican, Zulkifli Merican Aljunid; Bhat, Aamir Hussian; Hoe, Beh Guan; Sulaimon, Aliyu Adebayo; Akbarzadeh, Omid; Khan, Muhammad Saad; Mukhtar, Ahmad; Saqib, Sidra; Hameed, Ayesha; Mellon, Nurhayati; Ullah, Hafeez; et al. (Elsevier, 2019)
Despite the remarkable nanofluids potential in energy storage applications, the long-term dispersion stability of the nanoparticles in a base fluid along with improved thermal conductivity is a significant challenge towards their commercialization. Therefore, a novel surfactant MWCNTs and eco-friendly Jatropha seed oil based nanofluid are synthesized via one-step synthesis method and subjected to characterization via visual analysis, FTIR, Zeta potential, pore size distribution, thermogravimetric analysis (TGA), and UV analysis to investigate MWCNTs dispersion stability along with thermal conductivity measurement. The results showed the excellent MWCNTs dispersion stability in Jatropha seed oil and thermal conductivity improvement from 2.29% to 6.76% over the temperature within the range of 25–65 °C and nanoparticle weight fraction in the range of 0.2–0.8 wt%. Furthermore, two new correlations are proposed based on multiple non-linear regression analysis and dimensionless group analysis in the replacement of classical models which are failed to accurate prediction of thermal conductivity. The developed models showed remarkable thermal conductivity prediction accuracy with the value of R2 > 0.991. © 2019